Modelling the effect of distributed battery energy storage in an isolated power system. (15th January 2023) - McIlwaine, Neil; Foley, Aoife M.; Best, Robert; Morrow, D. John; Kez, Dlzar Al
Abstract: Wind generation is often curtailed in isolated power systems to ensure system operational security. This happens during periods of high wind generation and low system demand. This research investigates the effect of battery storage deployed in an isolated power system with a high share of renewables, on the total cost of generation, emissions levels, ramping time, and excess energy. A commercial unit commitment software package is used to model the Northern Ireland power system at various levels of battery storage using actual load, wind, and generator data. The results from the study confirm that for a high load month, deployment of battery energy storage can reduce the total cost of generation by 2.5%, reduce the emissions by 11%, reduce ramping time by 52%, and dump energy by 0.5% of total demand. The conclusion reached is that battery storage will become a key piece of infrastructure for low carbon power systems. Highlights: Quantify the effects of battery energy storage in an isolated power system. Create an electricity system with different scenarios of wind and storage. Modelled using unit commitment/dynamic economic dispatch software. Storage is beneficial to the operation of existing fossil fuelled generation. Storage facilitates renewables and enhances existing generation.